Climate justice and feasibility - Hunter, Taylor, author; Shockley, Ken, advisor; McShane, Katie, committee member; Carolan, Michael, committee member (Colorado State University. Libraries, 2021)
The primary motivation for this Thesis is to understand whether it is in fact feasible for rich countries, like the United States, to fulfill their humanitarian obligations through an international climate treaty. And if this is infeasible, why? Alongside this motivation, is a motivation to bring to light another important dimension to climate justice that is often lost within the scale and the urgency of climate change, namely the misrecognition of Indigenous peoples. My task in Chapter One is to explain how Eric Posner's and David Weisbach's employment of the political feasibility constraint of International Paretianism functions in international climate policy discourse. I work to show how climate policy outcomes solely constrained by International Paretianism will predictably violate basic humanitarian constraints. Posner and Weisbach defend a Two-Track Approach to climate policy, where the ends of justice are best achieved though policy means independent of a climate treaty. Their view entails that climate policies should not be designed with regard to constraints of justice. Rather than satisfy constraints of justice, a climate treaty need only satisfy the political feasibility constraint of International Paretianism. I work to show the policy outcomes that follow from the feasibility constraint of International Paretianism, which are morally unacceptable because they violate basic humanitarian obligations. Posner and Weisbach justify these moral costs by appealing to what is and what is not politically feasible, per International Paretianism. I will work investigate the legitimacy of this feasibility constraint in Chapter Two. My task in Chapter Two is to investigate the political legitimacy of International Paretianism. I begin by clarifying how feasibility constraints function in normative theorizing and I defend what I consider to be an appropriate function for International Paretianism. There are two general functions that feasibility constraints can serve in policy decision making. Hard feasibility constraints function to rule out policy outcomes that are in principle impossible due to invariant conditions, while soft feasibility function inform our practical deliberations about what we can do given our contingent circumstances. Soft constraints allow us to acknowledge that there are limits on what we can realistically accomplish, while also acknowledging that we can work to change these limits. In this Chapter, I will argue that we should not make the mistake of using International Paretianism as a hard constraint. I will argue that it is conceptually possible for states to act for reasons other than the common interest of their citizenry. As such, International Paretianism is a soft feasibility constraint. I conclude with an analysis of why it is that International Paretianism is a soft feasibility constraint for the United States. My task Chapter Three is to present one possible way that institutions can govern themselves towards an interdependent collective continuance, and to identify a soft feasibility constraint that is relevant to the ability of US federal agencies to integrating such institutional capacities. Indigenous people have an epistemic advantage on how to respond to climate change, and in an ameliorative way. Yet, they are not procedurally or culturally recognized for their knowledge. I consider this to be a constraint on our ability to appropriately respond to climate change. In this Chapter, I will present the way in which the Potawatomi Nation, members of the Anishinaabe Intellectual Tradition, have and continue to interdependently govern themselves toward collective continuance. I will argue that Indigenous peoples in fact have an epistemic advantage in this particular subject matter, which is due to a long history of colonially-induced ecological displacement and relocation. I will conclude by identifying and defending what I believe to be a 'soft' cultural feasibility constraint on the ability of federal agencies to work in reciprocal relations of knowledge exchange with Indigenous peoples at the procedural level of climate policy decision-making. The normative upshots of this Thesis are that (1) the citizens of the United States have a responsibility to change their government institutions such that they can be responsive to humanitarian constraints, as well as ecological limits. And (2) one way in which this responsibility may be realized is through members of the United States correcting for an identity prejudice that would preempt the United States government from instituting reciprocal relations of knowledge exchange with Indigenous people.
Keywords: feasibility; International Paretianism; climate justice; traditional ecological knowledge; Indigenous justice